Análise da força propulsora do motor de indução linear alimentado com imposição de corrente - Alves, Thiago Berger Canuto (2016)
This work intent to study the motive power provided by the plane linear induction motor, in a lock condition. It uses a method of imposition of the electric current to the stator via a frequency convertor PWM driven by a refed platform. The reading of the motive power was performed by a load cell using an electronic circuit for reading and conditioning of the signal. Aiming a complete analysis of the linear motor, it was performed a computational modeling that employs all relevant parameters to the study of the locked machine. At the end it was held a theoric-experimental confrontation that evaluated the effectiveness of the proposed method.